Systematic and meta-based evaluation on job satisfaction of village doctors: An urgent need for solution issue - Chen, Yuquan; You, Yanwei; Wang, Yue; Wang, Yudong; Dai, Tao (Frontiers in Medicine, 2022)
Village doctors are the health "gatekeepers" of rural residents in most developing countries. They undertake a series of strenuous but pivotal missions, including prevention, diagnosis, and treatment of complicated diseases, sanitation services and management, preventive health care and education tasks, etc. Hence, it is of great importance to evaluate the village doctors' job satisfaction status, which is one of the most important indicators that can reflect the current working state, to provide guidelines for the health care policies. The literature search was conducted in 7 authoritative databases, including PubMed, EMBASE, Web of Science, China National Knowledge Infrastructure(CNKI), etc. Experts in the field of social medicine were consulted to achieve supplement and obtain relevant literature. China was selected as a representative of the village doctor system for the in-depth analysis. Building on the previous literature, we modified and proposed a novel strategy which can transform and integrate the outcome indicators to conduct a meta-based and quantitative assessment on job satisfaction. A total of 37 publications and 23,595 village doctors were included in this research. After the adjustment of publication bias,the overall job satisfaction score of village doctors was 2.7579, 95% CI: 2.5254~2.9904, which indicated a direct "dissatisfied" level. To discover the underlying causes, a holistic analysis of each dimension and influencing factors of job satisfaction were conducted and the results demonstrated that ‘Financial Rewards’ (2.49) was the most important factor causing dissatisfaction among village doctors, followed by ‘Job Security (2.52)’ and ‘Work Stress (3.05)’. Several important themes were also identified and assessed to explore the factors related to this topic. This study indicated that there is an urgent need to improve the working status of health workers in rural and remote areas, especially in the middle-and low-income countries. Health policy makers should not only improve the current remuneration and subsidies of village doctors, but also guide the professional development, and give them more job security to enhance the work stability of this group. More specifically, in the context of COVID-19 pandemic, further surveys on job satisfaction of village doctors should be carried out to take targeted measures.